Community‐wide correlations between species richness, abundance and population genomic diversity in a freshwater biodiversity hotspot - Jamie R. Bucholz; Garrett W. Hopper; Irene Sánchez González; Taylor E. Kelley; Colin R. Jackson; Ryan C. Garrick; Carla L. Atkinson; Jeffrey D. Lozier (Molecular Ecology, 2023)
Understanding patterns of diversity across macro (e.g. species‐level) and micro (e.g. molecular‐level) scales can shed light on community function and stability by elucidating the abiotic and biotic drivers of diversity within ecological communities. We examined the relationships among taxonomic and genetic metrics of diversity in freshwater mussels (Bivalvia: Unionidae), an ecologically important and species‐rich group in the southeastern United States. Using quantitative community surveys and reduced‐representation genome sequencing across 22 sites in seven rivers and two river basins, we surveyed 68 mussel species and sequenced 23 of these species to characterize intrapopulation genetic variation. We tested for the presence of species diversity–abundance correlations (i.e. the more‐individuals hypothesis, MIH), species‐genetic diversity correlations (SGDCs) and abundance‐genetic diversity correlations (AGDCs) across all sites to evaluate relationships between different metrics of diversity. Sites with greater cumulative multispecies density (a standardized metric of abundance) had a greater number of species, consistent with the MIH hypothesis. Intrapopulation genetic diversity was strongly associated with the density of most species, indicating the presence of AGDCs. However, there was no consistent evidence for SGDCs. Although sites with greater overall densities of mussels had greater species richness, sites with higher genetic diversity did not always exhibit positive correlations with species richness, suggesting that there are spatial and evolutionary scales at which the processes influencing community‐level diversity and intraspecific diversity differ. Our work reveals the importance of local abundance as indicator (and possibly a driver) of intrapopulation genetic diversity.